1972
DOI: 10.1002/cpt1972134584
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral aromatic l‐amino acids decarboxylase inhibitor in parkinsonism. II. Effect on metabolism of l‐2‐14C‐dopa

Abstract: The effects of MK‐486, an inhibitor of peripheral aromatic l‐amino acids decarboxylase, on certain urinary metabolites derived from orally administered l‐2‐14C‐dopa were studied in 3 patients with Parkinson's disease. Each patient received, after an overnight fast, 50 p.c of l‐2‐14C‐dopa (100 mg.). Urine and blood were collected serially and assayed for dopa and its major metabolites. This metabolic profile was compared with that obtained after the same dose of l‐2‐14C‐dopa but following pretreatment with MK‐4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Moreover, we have found that administration of pyridoxine during treatment with levodopa and carbidopa (MK-486) to two Parkinsonian patients, initially decreased the excretion of levodopa major metabolites and thus failed to increase the same as without carbidopa (18). The latter exert an inhibitory effect on extracerebral decarboxylation of levodopa ( 19,20). All these findings are compatible with the postulate that pyridoxine enhances or accelerates the decarboxylation of DOPA to DA and may explain the mechanism by which pyridoxine negates the therapeutic efficacy of levodopa.…”
supporting
confidence: 63%
“…Moreover, we have found that administration of pyridoxine during treatment with levodopa and carbidopa (MK-486) to two Parkinsonian patients, initially decreased the excretion of levodopa major metabolites and thus failed to increase the same as without carbidopa (18). The latter exert an inhibitory effect on extracerebral decarboxylation of levodopa ( 19,20). All these findings are compatible with the postulate that pyridoxine enhances or accelerates the decarboxylation of DOPA to DA and may explain the mechanism by which pyridoxine negates the therapeutic efficacy of levodopa.…”
supporting
confidence: 63%
“…The impact of decarboxylase inhibitors on latency to peak concentrations varies in the reported literature. This has been found to be either shorter, 26 similar, 10 12 29 or longer 9 compared with L-dopa alone, and one study 28 found a dose-dependent reduction in T max in the presence of CD. Although the delay to maximum plasma concentration of 95.5 min found in our study appears rather long, similar delays on standard release LD/decarboxylase inhibitor have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Orally administered levodopa is 95% metabolized outside the brain (Bianchine et al, 1972). The major metabolic pathway is by decarboxylation.…”
Section: Resultsmentioning
confidence: 99%